2020
DOI: 10.1590/0037-8682-0579-2020
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patients with Covid-19 hospitalized in southern Santa Catarina

Abstract: Introduction: Coronavirus disease 2019 (COVID-19), a potentially fatal disease, is caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The number of cases has increased rapidly, but information on the clinical characteristics remains limited. Methods: Cohort study. We collected and analyzed epidemiological, demographic, and clinical data of critically and noncritically ill patients and compared the outcomes. Results: The mean age of hospitalized patients with COVID-19 was 54 years (stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
3
5
0
2
Order By: Relevance
“…The results of this study demonstrated that patients over 60 years old with associated comorbidities had worse COVID-19 prognosis, as in the study by Li et al 12 , Schuelter-Trevisol et al 13 and Tan et al 14 . In the systematic review by Tan et al 14 , critically ill patients with COVID-19 had an average age of 62.6 years.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results of this study demonstrated that patients over 60 years old with associated comorbidities had worse COVID-19 prognosis, as in the study by Li et al 12 , Schuelter-Trevisol et al 13 and Tan et al 14 . In the systematic review by Tan et al 14 , critically ill patients with COVID-19 had an average age of 62.6 years.…”
Section: Discussionsupporting
confidence: 78%
“…According to Suleyman et al 24 , 39.7% of their patients needed ICU hospitalization in a New York hospital, similar to the percentage found in this study. In another hospital with similar characteristics 13 , 29% of the patients needed to be admitted to the ICU; in a private hospital, the need for ICU hospitalization was 33% 8 . Some factors are considered to be associated with the slightly superior percentage found in this study, such as factors related to the higher incidence of comorbidities in our patients because they are socioeconomically disadvantaged, being dependent on the Brazilian Unified Health System (SUS), therefore facing more significant challenges in getting medical care and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The determining criterion for the severity of the disorder was the presence or absence of hypoxia (25). COVID-19 affected all age groups; however, people over the age of 60 had the worst prognosis leading to death (26). At the time of the pandemic, measures were taken which led to social isolation, loss or risk of Clinical Social Work and Health Intervention Vol.…”
Section: Covid -19mentioning
confidence: 99%
“…A senescência, processo natural do envelhecimento ao nível celular e fatores associados, torna o grupo populacional dos idosos um dos mais suscetíveis tanto pelas disfunções imunológicas quanto pelas alterações fisiológicas que afetam os diversos sistemas do organismo, somando-se ao uso concomitante e rotineiro de vários medicamentos. Tais condições são responsáveis pela fragilidade e consequente agravamento do estado de saúde geral desse grupo, fato que tem sido observado pelo alto índice de internações em UTI e óbitos entre os idosos (SCHUELTER-TREVISOL et al, 2020).…”
Section: Fundamentação Teóricaunclassified
“…Além disso, algumas comorbidades estão relacionadas com maior suscetibilidade ao agravamento e necessidade de admissão na UTI, destacando-se: a Hipertensão Arterial Sistêmica (HAS), doenças neurológicas ou psiquiátricas e dislipidemia. Já os fatores concernentes a idade avançada, obesidade e doenças pulmonares crônicas apresentam riscos consideráveis para um mau prognóstico e transferência para UTI (SCHUELTER-TREVISOL et al, 2020).…”
Section: Fundamentação Teóricaunclassified